A Scalable Numerical Method for Simulating Flows Around High-Speed Train Under Crosswind Conditions (Communications in Computational Physics, 2020)
This paper presents a parallel Newton-Krylov-Schwarz method for the numericalsimulation of unsteady flows at high Reynolds number around a high-speedtrain under crosswind. With a realistic train geometry, a realistic Reynolds number,and a realistic wind speed, this is a very challenging computational problem. Becauseof the limited parallel scalability, commercial CFD software is not suitable forsupercomputers with a large number of processors. We develop a Newton-Krylov-Schwarzbased fully implicit method, and the corresponding parallel software, for the3D unsteady incompressible Navier-Stokes equations discretized with a stabilized finiteelement method on very fine unstructured meshes. We test the algorithm andsoftware for flows passing a train modeled after China's high-speed train CRH380B,and we also compare our results with results obtained from commercial CFD software.Our algorithm shows very good parallel scalability on a supercomputer with over onethousand processors.